2019
DOI: 10.14814/phy2.14234
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T cell activation and associated susceptibility to HIV‐1 infection in vitro increased following acute resistance exercise in human subjects

Abstract: Early studies in exercise immunology suggested acute bouts of exercise had an immunosuppressive effect in human subjects. However, recent data, show acute bouts of combined aerobic and resistance training increase both lymphocyte activation and proliferation. We quantified resistance exercise‐induced changes in the activation state of CD4+ T lymphocytes via surface protein expression and using a medically relevant model of infection (HIV‐1). Using a randomized cross‐over design, 10 untrained subjects completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Since OX40 promoted IL-9 production of MAIT cells, we then examined whether OX40 facilitated MAIT cell activation in H. pylori -induced gastritis, as what we found in T2D patients ( 11 ). As expected, OX40 + MAIT cells from H. pylori gastritis patients were found to express high levels of CD69 and CD25 ( Figures 3A,B ), which are T cell activating markers ( 29 , 30 ). Meanwhile, a positive correlation was observed between the percentage of OX40 + T cells and MAIT cells ( Figure 3C ), indicating that OX40 may promote MAIT cell proliferation.…”
Section: Resultssupporting
confidence: 80%
“…Since OX40 promoted IL-9 production of MAIT cells, we then examined whether OX40 facilitated MAIT cell activation in H. pylori -induced gastritis, as what we found in T2D patients ( 11 ). As expected, OX40 + MAIT cells from H. pylori gastritis patients were found to express high levels of CD69 and CD25 ( Figures 3A,B ), which are T cell activating markers ( 29 , 30 ). Meanwhile, a positive correlation was observed between the percentage of OX40 + T cells and MAIT cells ( Figure 3C ), indicating that OX40 may promote MAIT cell proliferation.…”
Section: Resultssupporting
confidence: 80%
“…These results suggested that S. japonicum infection could induce strong immune response in intestinal tract. CD25 and CD69 were classic markers for T cell activation [33], though CD4 + CD25 + foxp3 + T cells were served as nature regulatory T cells (Treg) [35], and CD69 was seem to be a marker for tissue resident memory T cells (TRM) [36]. Higher percentages of CD25 and CD69-expressing CD3 + T were found in the infected mouse MLN.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the number of MLN mononuclear cells in response to infection dramatically increased, the absolute number of MLN CD3 + T cells was obviously increased after infection (P < 0:05, Figure 1(e)). CD25 and CD69 were classic markers for T cell activation [33]. To detect the degree of activation, the expression of CD25 and CD69 on CD3 + T cells was detected by the cell surface staining.…”
Section: Accumulation Of Cd3 + T Cells In Infected Mesentericmentioning
confidence: 99%
“…Even though the difference between the two exercise protocols was not statistically significant, cholesterol levels and CD69 expression in CD8 + T cells increased significantly after continuous exercise, predominantly in moderately fit donors. As early marker for VSTs activation [61], the observed increases in CD69 and cholesterol correlated well with higher IFN-γ secretion. In a comprehensive future study, we will investigate the impact and modulatory role of cholesterol on VST activation and function.…”
Section: Discussionmentioning
confidence: 67%